Differential efficacy of nicotine replacement among overweight and obese women smokers. - Strong, DR; David, S; Johnstone, E; Aveyard, P; Murphy, M; Munafò, M (2014)
Introduction Rates of obesity are higher among more dependent smokers and 37-65% of smokers seeking cessation treatment are overweight or obese. Overweight or obese smokers may possess metabolic and neurobiological features that contribute to difficulty achieving cessation using front-line nicotine replacement products. Attention to factors that facilitate effective cessation treatment in this vulnerable population is needed to significantly reduce mortality risk among overweight and obese smokers. Method This secondary analysis of two large trials of transdermal nicotine replacement in general medical practices evaluated the hypothesis that higher body mass index (BMI) would moderate the efficacy of the nicotine patch. We examined the potential for gender to further moderate the relationship between BMI and treatment efficacy. Results In the placebo controlled trial (N=1,621), 21 mg patch was no more effective than placebo for assisting biochemically verified point prevalence abstinence up to one-year after quitting for women with higher BMI, but appeared to be effective for men at normal or high BMI (gender x BMI beta = -0.22, p = 0.004). We did not find differential long-term cessation outcomes among male or female smokers in the 15mg patch trial (n=705). However, we observed significantly higher rates of early lapse among women with higher BMI treated with nicotine patch across both trials. Conclusion These results suggest that increased BMI may affect the efficacy of nicotine patch on reducing risk of early lapse in women. Additional research is needed to explore mechanisms of risk for decreased efficacy of this commonly used cessation aid.